2007
DOI: 10.1136/jnnp.2006.105940
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase gene mutation is a risk factor for early onset of Parkinson disease among Taiwanese

Abstract: Background: Mutations in the glucocerebrosidase (GBA) gene have recently been identified as contributing to the development of Parkinson disease (PD) in Ashkenazi Jews. Methods: To investigate whether this finding can be confirmed in a Taiwanese population, we conducted a case control study in a cohort of 518 PD patients and 339 controls for the three common GBA mutations in Taiwan, L444P, RecNciI and R120W, using PCR restriction enzyme assay and DNA sequencing. Results: Heterozygous GBA mutations were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
69
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 15 publications
13
69
3
Order By: Relevance
“…11 A large study of both Jewish and non-Jewish samples found an association between GBA mutations and PD in the Jewish group only. 15 Chinese patients with PD from Singapore demonstrated a significant association with GBA, 21 whereas a similar study of Chinese patients from Taiwan did not. 20 A survey of Italian patients with PD for the N370S and L444P mutations found a significant association of these variants with PD, 22 while a Norwegian sample showed comparable frequencies of these two mutations in patients with PD and controls.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…11 A large study of both Jewish and non-Jewish samples found an association between GBA mutations and PD in the Jewish group only. 15 Chinese patients with PD from Singapore demonstrated a significant association with GBA, 21 whereas a similar study of Chinese patients from Taiwan did not. 20 A survey of Italian patients with PD for the N370S and L444P mutations found a significant association of these variants with PD, 22 while a Norwegian sample showed comparable frequencies of these two mutations in patients with PD and controls.…”
mentioning
confidence: 91%
“…23 In some studies, patients with PD harboring GBA variants had earlier age at disease onset. 12,15,19,21 Whether the discrepant results regarding the association of GBA with disease and age at onset result from true ethnic differences in GBA variant frequencies or from differences in the scope of the studies (i.e., only screening for certain variants as opposed to sequencing the entire coding region) remains to be determined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Founder mutations in GBA can be detected in 1 out of 16 Ashkenazi Jews, and were shown to be important risk factors for Parkinson disease (PD) in this population 2,3 and in many other populations worldwide. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Three other lysosomal storage diseases that are caused by founder mutations can be found in the AJ population: Tay-Sachs disease 19 (carrier frequency of 1:27 20 ), Niemann-Pick disease type A 21 (1:115 20 ), and mucolipidosis type IV 22 (1:89 20 ). These 3 autosomal recessive diseases are caused by mutations in genes encoding lysosomal enzymes, 23 and their deficiency results in cellular accumulation of the enzymes' substrates.…”
mentioning
confidence: 99%